2018
DOI: 10.1302/0301-620x.100b12.bjj-2018-0189.r2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for local recurrence in extremity-located giant cell tumours of bone with pathological fracture

Abstract: Aims The aim of this paper was to investigate the prognostic factors for local recurrence in patients with pathological fracture through giant cell tumours of bone (GCTB). Patients and Methods A total of 107 patients presenting with fractures through GCTB treated at our institution (Royal Orthopaedic Hospital, Birmingham, United Kingdom) between 1995 and 2016 were retrospectively studied. Of these patients, 57 were female (53%) and 50 were male (47%).The mean age at diagnosis was 33 years (14 to 86). A univari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 19 publications
0
48
0
Order By: Relevance
“…There is no clear information regarding the optimal surgical treatment of GCTB presenting with a pathological fracture. 10,12,22,29,36 Therefore, we performed this study to evaluate the local recurrence rates, function, and complications after curettage versus resection for GCTB presenting with pathological fractures. Our results showed similar local recurrence and complication rates but better function with curettage versus resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no clear information regarding the optimal surgical treatment of GCTB presenting with a pathological fracture. 10,12,22,29,36 Therefore, we performed this study to evaluate the local recurrence rates, function, and complications after curettage versus resection for GCTB presenting with pathological fractures. Our results showed similar local recurrence and complication rates but better function with curettage versus resection.…”
Section: Discussionmentioning
confidence: 99%
“…Giant cell tumor of bone (GCTB) accounts for approximately 5% of all primary bone tumors . The rate of pathological fracture at presentation in these patients is 4% to 50% . In the presence of a pathological fracture, treatment with curettage may be difficult and may lead to a higher local recurrence rate because of tumor contamination of adjacent soft tissues and joint by the hematoma .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is argued that the newly formed peripheral bone rim and hardened tumor tissue reduced the risk of inadvertent contamination [19]. Although we did not acquire sufficient data to conduct pooled-analysis on the outcome of denosumab combining curettage and local adjuvant, it is strongly recommended in many studies to use local adjuvant and high speed burr [3,24,26,27].Most studies included in our analysis applied various methods of local adjuvant in most patients except for one study specified that no local adjuvant was used [20].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical choice was taken into account by comparing cases underwent curettage with denosumab and curettage alone in 4 studies [9,[16][17][18](OR: 2.13, 95% CI: 0.95 to 4.76, p=0.07, I 2 =29%)( Figure 3), though the result was not statistically significant. 7 studies [9,[15][16][17][18][19][20] reported outcome on primary lesions, which also suggest significantly higher risk of local recurrence in the denosumab group(OR: 1.91, 95% CI: 1.17 to 3.09, p=0.009, I 2 =36%)( Figure 4).…”
Section: Recurrencementioning
confidence: 99%
“…3), though the result was not statistically significant. Seven studies [9,[15][16][17][18][19][20] reported outcome on primary lesions, which also suggest significantly higher risk of local recurrence in the denosumab group (OR: 1.91, 95% CI: 1.17 to 3.09, p = 0.009, I 2 = 36%)( Fig. 4).…”
Section: Recurrencementioning
confidence: 99%